Altered andragogy: lessons from lockdown for systems engineering education - Barker, Stephen G.; Smith, Jeremy D. (The International Academic Forum (IAFOR), 2021)
Systems Engineering (SE) is a largely interactive and applied discipline which has been mainly taught via face-to-face tuition. The move to online-only teaching due to the 2020 coronavirus pandemic thus posed significant challenges for SE education. The andragogical strategy involved had to be rethought and redesigned such that key precepts of student learning could be maintained in a way that preserved the depth, intricacy, and richness of the SE discipline. The interdisciplinary approach adopted involved combining a constructivist viewpoint with integrated collaborative and reflective activities, based around inquiry-based learning to facilitate online learning at distance. This pedagogical construct relied on a multidisciplinary and iterative approach to curriculum and module delivery, employing multiple methods to redesign the teaching approach to ‘chunk’ material into sets that were more readily deliverable in short bursts, and more digestible without face-to-face interaction. This took in revisions to the traditional pedagogical approach to learning, and blended short live online sessions with self-paced tasks, supported by Q&A sessions and ‘thought bursts’ of key information to summarise key learning points. Learning technology and software tools were used to facilitate and promote interactive and group workshops, which was particularly challenging but proved useful in bridging generational gaps and preferences for certain learning styles. This paper details the andragogical approach taken to wholly online distance learning for SE, reflecting on how successful it was both initially and as it evolved. It also considers how future learning can be successfully facilitated, incorporating the pedagogical lessons learned from the last twelve months.
Keywords: Andragogy; Systems Engineering; Teaching Practice